A Fiber Bragg Grating—Bimetal Temperature Sensor for Solar Panel Inverters - Ismail, Mohd Afiq; Tamchek, Nizam; Abu Hassan, Muhammad Rosdi; Dambul, Katrina D.; Selvaraj, Jeyrai; Abd Rahim, Nasrudin; Sandoghchi, Reza; Mahamd Adikan, Faisal Rafiq (MDPI, 2011)
This paper reports the design, characterization and implementation of a Fiber Bragg Grating (FBG)-based temperature sensor for an Insulted-Gate Bipolar Transistor (IGBT) in a solar panel inverter. The FBG is bonded to the higher Coefficient of Thermal Expansion (CTE) side of a bimetallic strip to increase its sensitivity. Characterization results show a linear relationship between increasing temperature and the wavelength shift. It is found that the sensitivity of the sensor can be categorized into three characterization temperature regions between 26 degrees C and 90 degrees C. The region from 41 degrees C to 90 degrees C shows the highest sensitivity, with a value of 14 pm/degrees C. A new empirical model that considers both temperature and strain effects has been developed for the sensor. Finally, the FBG-bimetal temperature sensor is placed in a solar panel inverter and results confirm that it can be used for real-time monitoring of the IGBT temperature.